Análisis del comportamiento del oxígeno disuelto y la demanda química de oxígeno en tres puntos (Lasso, Latacunga, Salcedo) del rio Cutuchi, en la provincia de Cotopaxi, cantón Latacunga, periodo 2013 - 2014 - Lamingo LLumiquinga, Jessica Patricia (2014)
Water has been always the most important way used by the man for the elimination of generated residues about its activity. The high economic development and population expantion have increased such a impact of the man over Cutuchi river water, it has overcome widely its autopurification capacity, it has brought as consequence a low water quality, therefore, the decreasing of the water as resource. The research was executed by samples collectied in three points of the Cutuchi river, the first sample was took in Lasso in Callo Mancheno sector, with next coordinates: Latitude 9916610 N, Length 766269 and, Altitude 2989 O.S. with the following results: Oxygen Dissolved 5,75 mg/l and Chemical Demand of Oxygen <10,0 mg/l, the second sample was took in Latacunga Baño Azúl sector, with the following coordinates: Latitude 9895739 N, Length 765467 and, Altitude 2743 O.S. with next....